The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.neuropharm.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Removing TRPV1-expressing primary afferent neurons potentiates the spinal analgesic effect of δ-opioid agonists on mechano-nociception

Abstract: Most δ-opioid receptors are located on the presynaptic terminals of primary afferent neurons in the spinal cord. However, their presence in different phenotypes of primary afferent neurons and their contribution to the analgesic effect of δ-opioid agonists are not fully known. Resiniferatoxin (RTX) is an ultra-potent transient receptor potential vanilloid type 1 channel (TRPV1) agonist and can selectively remove TRPV1-expressing primary afferent neurons. In this study, we determined the role of δ-opioid recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…As described previously [7, 10, 36], TRPV1-ir was concentrated in lamina I and the inner part of lamina II (Fig 6). Two-way ANOVA revealed that nerve injury decreased TRPV1-ir [F(3,57)=9.8, P<0.0001].…”
Section: Resultssupporting
confidence: 79%
“…As described previously [7, 10, 36], TRPV1-ir was concentrated in lamina I and the inner part of lamina II (Fig 6). Two-way ANOVA revealed that nerve injury decreased TRPV1-ir [F(3,57)=9.8, P<0.0001].…”
Section: Resultssupporting
confidence: 79%
“…Thus, TRPV1‐expressing dorsal horn neurons may be involved in the amplification of nociceptive input from primary afferents. We have shown that this subpopulation of dorsal horn neurons is endowed with μ‐opioid, but not δ‐opioid, receptors (Chen and Pan 2006, 2008). Our finding is consistent with the previous study showing that μ‐opioid receptors are expressed only on non‐GABAergic and non‐glycinergic neurons in the spinal cord (Kemp et al.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies had suggested that the different types of opioid receptors, particularly MOPR and DOPR, were coexpressed by the same class of DRG neurons, namely unmyelinated peptidergic nociceptors. These neurons detect noxious stimuli in skin and internal organs and express the neuropeptides substance P and calcitonin gene-related protein (CGRP) and the heat-and capsaicin-sensitive transient receptor potential cation channel subfamily V member 1 (TRPV1) (Chen & Pan 2008, Ueda 2006, Vetter et al 2006). MOPR expression in these cells is thought to contribute to the remarkable utility of mu agonists for perioperative pain management (Figure 2c).…”
Section: Neuroanatomical Substrates For Opioid Analgesiamentioning
confidence: 99%